2017
DOI: 10.1037/met0000101
|View full text |Cite
|
Sign up to set email alerts
|

Item response theory scoring and the detection of curvilinear relationships.

Abstract: Psychologists are increasingly positing theories of behavior that suggest psychological constructs are curvilinearly related to outcomes. However, results from empirical tests for such curvilinear relations have been mixed. We propose that correctly identifying the response process underlying responses to measures is important for the accuracy of these tests. Indeed, past research has indicated that item responses to many self-report measures follow an ideal point response process-wherein respondents agree onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 29 publications
0
36
0
Order By: Relevance
“…Personality trait domains generally are conceptualized in terms of variance shared by facets; however, facets themselves have unique variance, which may be accounted for by other personality domains (e.g., Bäckstr€ om, Larsson, & Maddux, 2009) or unique constructs. Finally, recent research (Carter et al, 2016) has demonstrated an advantage for ideal point item response modeling for detecting curvilinear relationships between traits and functioning; however, such methods require larger sample sizes and, based on previous results (Carter, Dalal, Guan, LoPilato, & Withrow, 2017;Carter et al, 2016), such scoring methods alone likely would not have grossly altered the present findings.…”
Section: MI Ta Ti Onsmentioning
confidence: 72%
“…Personality trait domains generally are conceptualized in terms of variance shared by facets; however, facets themselves have unique variance, which may be accounted for by other personality domains (e.g., Bäckstr€ om, Larsson, & Maddux, 2009) or unique constructs. Finally, recent research (Carter et al, 2016) has demonstrated an advantage for ideal point item response modeling for detecting curvilinear relationships between traits and functioning; however, such methods require larger sample sizes and, based on previous results (Carter, Dalal, Guan, LoPilato, & Withrow, 2017;Carter et al, 2016), such scoring methods alone likely would not have grossly altered the present findings.…”
Section: MI Ta Ti Onsmentioning
confidence: 72%
“…In this study, we applied item response theory (IRT), structural equation modeling (SEM), and logistic regression analysis to infer the required proficiency levels of the daily jobs of Japanese dental hygienists and the relationship between their daily jobs and motivation to work. e benefits of IRT include comprehensive analyses, a reduction in measurement errors, the ability to create tests or questionnaires, meaningful scaling of latent variables, objective calibrations and equating, evaluations of tests or questionnaires and item biases, high accuracy in assessments, and evaluations of models and person-fit models [16]. IRT refers to a family of mathematical models that attempt to explain the relationships between latent traits and their manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…A key analytical advance in the article by Williams and Simms () is the examination of predictive bipolarity—or the nonlinear relations between the traits and outcomes. Nonetheless, even this effort was likely limited in their study since methodological work has suggested that ideal point scoring, as opposed to the typical dominance methods (e.g., total score, factor scores) that they used, is necessary for fully uncovering predictive bipolarity when it is present (Carter, Dalal, Guan, LoPilato, & Withrow, ). Future work should continue to examine how the response process, including ideal point scoring, influences findings for psychometric and predictive bipolarity.…”
Section: Future Research Directions For Investigating Bipolaritymentioning
confidence: 99%